The Poor Passing Standard of Healthcare Workers with the National Competence Examination for Indonesian Health Professionals - Jumita Jumita; Sudarwan Danim; Muhammad Kristiawan; Zulqurnain Sabir; David D. Perrodin (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This research aimed to provide an overview of the poor passing standard of the National Competence Examination for Indonesian Health Professionalswith healthcare workers in Bengkulu City, Indonesia. This review used a mixed method with sequential exploratory approach, resulting in a collection of studies gathering and evaluating data to clarify research problems.The subjects of this research were alumni of the D-III Midwifery Study Program at the Dehasen University of Bengkulu who had taken competence examinations.Data fromten participants who took part in the test competenceexaminationwere analyzed using thematic analysis.The findings showed variables, including the prevalence of trials, the value of the GPA, learning styles, motivation, and consistency when taking the tests, influenced the poor passing standard of the healthcare worker competency test.It was expected that to raise the percentage, the Ministry of Research, Technology and Higher Education and Higher Education of the Republic of Indonesiashould run more programs through higher education.